Multilevel view on chromatin architecture alterations in cancer - Gridina, Maria; Fishman, Veniamin (Frontiers in Genetics, 2022)
Chromosomes are not located inside the nucleus in the form of linear molecules. Instead, there is a complex multilevel genome folding that includes nucleosomes, topologically associating domains, compartments, and finally, chromosomal territories. Proper spatial organization is essential for the correct functioning of the genome, and is therefore subject to change during development or disease. Here we discuss exactly how the organization of the cancer cell genome is different from the healthy genome on various levels. A better understanding of how malignization affects genome organization and long-range gene regulation will help reveal the molecular mechanisms underlying cancer development and evolution.